Formation of two-dimensional laser-induced periodic surface structures on titanium by GHz burst mode femtosecond laser pulses - Kawabata, Shota; Bai, Shi; Obata, Kotaro; Ozasa, Kazunari; Miyaji, Godai; Sugioka, Koji (Frontiers in Nanotechnology, 2023)
GHz burst mode femtosecond (fs) laser pulses, which consist of a series of pulse trains with ultra-fast intervals of several hundred picoseconds, have offered distinct features for material processing compared to conventional irradiation of laser pulses (single-pulse mode). We apply GHz burst mode processing to fabricate laser-induced periodic surface structures (LIPSS) on the material surfaces. In our previous work for silicon (Si), we have found that GHz burst mode can create unique two-dimensional (2D) LIPSS composed of both parallel and perpendicular to the laser polarization direction. We proposed that the formation of 2D-LIPSS is attributed to the synergetic contributions of electromagnetic and hydrodynamic mechanisms. To further investigate more detailed formation mechanisms and explore practical applications, we employ titanium (Ti), whose properties are significantly different from Si. We demonstrate that GHz burst mode fs laser pulses (central wavelength: 1030 nm, intra-pulse width: 230 fs, intra-pulse repetition rate (an intra-pulse interval): 4.88 GHz (205 ps) and burst pulse repetition rate: 10 kHz) can also fabricate 2D-LIPSS on Ti surfaces. We attribute the dominant formation mechanism of 2D-LIPSS to the generation of hot spots with highly enhanced electric fields due to transient change of material properties during GHz burst pulse irradiation. Based on this speculation, properly tailoring the shapes of the burst pulse with an optimum intra-pulse number enables the creation of well-defined 2D-LIPSS. Furthermore, essentially homogeneous 2D-LIPSS can be formed in a large area by laser scanning of a focused fs laser beam with a stage scanning speed of 5 mm/s.